Key Drivers of Ethiopia‘s Digital Ecosystem: An Exploratory Factor Analysis Aligned with Sustainable Development Goals - Belay Sitotaw Goshu (Britain International for Academic Research (BIAR) Publisher, 2027)
Ethiopia's digital ecosystem has undergone rapid transformation following telecommunications liberalization and the launch of successive national digital strategies, yet systematic empirical research identifying its underlying drivers remains scarce. This study employs Exploratory Factor Analysis (EFA) to identify the latent dimensions driving the development of Ethiopia's digital ecosystem and to examine their alignment with the Sustainable Development Goals (SDGs). Drawing on secondary data synthesized from national policy frameworks, World Bank project documents, peer-reviewed literature, and industry reports, the analysis reveals a robust five-factor structure explaining 64.8% of total variance, with Cronbach's alpha coefficients ranging from 0.82 to 0.89 confirming strong internal consistency. The extracted dimensions comprise (1) Digital Infrastructure and Connectivity (24.4% variance), (2) Financial Inclusion and Digital Payments (15.4%), (3) Human Capital and Digital Literacy (11.3%), (4) Policy, Governance, and Institutional Framework (8.7%), and (5) Innovation and Entrepreneurship Ecosystem (6.0%). The hierarchical ranking establishes infrastructure as the dominant driver, followed by financial inclusion, human capital, governance, and innovation. These factors demonstrate substantial alignment with SDGs 1, 4, 8, 9, 10, 16, and 17, providing an evidence-based framework for tracing digital investments to measurable development outcomes. The findings contribute to understanding how digital transformation in a lower-middle-income African context can be systematically conceptualized, measured, and strategically prioritized, offering actionable implications for policymakers, development practitioners, and researchers seeking to accelerate inclusive and sustainable digital development.